Bowongso Coffee Shop; More Than Just A Holiday and Place for Rural Youth Lifestyle in Indonesia - Muryanti, Muryanti (Universitas Negeri Semarang, 2022)
Subsistence farming is the main job of farmers in Bowongso Village, Wonosobo, Indonesia. Coffee is one of the commercial crops since it provides much profits and changes the pattern of agricultural management. The purpose of this paper was to find out how the creativity of youth in rural areas plays a role in developing agricultural innovation. Data were obtained from interviews with members of farmer groups, farmers, and consumers of the Bowongso coffee shop. The results showed that the commercialization of agriculture needs to be improved in increasing innovation and production to maintain the prosperity of rural communities. The Bowongso Coffee Shop is an innovation in the development of the agricultural sector from upstream to downstream driven by young farmers who are members of the Bina Sejahtera farmer group. The teenagers make coffee as a commercial plant and coffee shop as a place to gather and discuss the development of farmer groups or agricultural conditions in the village. The social movement of rural teenagers plays a role in the development of agriculture where they run coffee shops as a way of life for rural communities that are not much different from urban communities and further improve the village economy.